Robust IDA‐PBC for underactuated mechanical systems subject to matched disturbances - Donaire, Alejandro; Romero, Jose Guadalupe; Ortega, Romeo; Siciliano, Bruno; Crespo, Martin (International journal of robust and nonlinear control, 2017)
Summary The problem of robustification of interconnection and damping assignment passivity‐based control for underactuated mechanical system vis‐à‐vis matched, constant, and unknown disturbances is addressed in the paper. This is achieved adding an outer‐loop controller to the interconnection and damping assignment passivity‐based control. Three designs are proposed, with the first one being a simple nonlinear PI, while the second and the third ones are nonlinear PIDs. While all controllers ensure stability of the desired equilibrium in spite of the presence of the disturbances, the inclusion of the derivative term allows us to inject further damping enlarging the class of systems for which asymptotic stability is ensured. Numerical simulations of the Acrobot system and experimental results on the disk‐on‐disk system illustrate the performance of the proposed controller. Copyright © 2016 John Wiley & Sons, Ltd.